Peningkatan Produktifitas Umkm Jamu Gendong Melalui Edukasi Digital Marketing Di Desa Losari - Lutfiyah, Izzatul; Winarti, Winarti; Faqih, Misbah Bahauddin; Antin, Nyimmas Darah; Zahrah, Anisa Atifatur Rahmania Fatimatuz; Alfiani, Yunita Adinda Sari (CV. ITTC INDONESIA, 2023)
The lack of knowledge of the local community in Losari Village, Ploso District, is one of the things that prompted writed to carry out this activity, namely by providing education on packaging and marketing of Jamu Gendong products. The method used is the ABCD (Asset Based Community Development) Method. This approach focuses on an inventory of assets in the community which are assumed to be very supportive of community empowerment activities. In order to develop the potential of local Jamu Gendong products, a problem-solving framework is implemented which includes three things. First, observations regarding production, packaging and marketing that are usually carried out by partners. Second, educating partners regarding good packaging methods. Third, Education to partners regarding digital-based marketing methods. Digital-based packaging and marketing education can be a new innovation for them to be applicable to society